Optimizing Enteral Nutrition for Growth in Pediatric Chronic Kidney Disease (CKD) - Nelms, Christina L. (Frontiers in Pediatrics, 2018)
Growth in pediatric Chronic Kidney Disease is important for long-term outcomes including final adult height and cognitive function. However, there are many barriers for children with chronic kidney disease to achieve adequate nutritional intake to optimize growth. This review highlights these unique concerns, including route of nutrition, dialysis contributions and biochemical indices. Fitting the enteral feeding to the patients’ needs involves choosing an appropriate product or products, limiting harmful nutrients in excess, notably aluminum, and altering for electrolyte and micronutrient needs. Unique adjustments to the enteral regimen include accommodating volume needs, optimizing macronutrient ratios, specific electrolyte adjustments, the blending of products together and adjustments made to consider patient and family psychosocial needs. When a holistic approach to medical nutrition therapy is applied, taking the above factors into consideration, adequate intake for growth of the child with CKD is achievable.